2018
DOI: 10.1093/gbe/evy266
|View full text |Cite
|
Sign up to set email alerts
|

Cycad Coralloid Roots Contain Bacterial Communities Including Cyanobacteria andCaulobacterspp. That Encode Niche-Specific Biosynthetic Gene Clusters

Abstract: Cycads are the only early seed plants that have evolved a specialized root to host endophytic bacteria that fix nitrogen. To provide evolutionary and functional insights into this million-year old symbiosis, we investigate endophytic bacterial sub-communities isolated from coralloid roots of species from Dioon (Zamiaceae) sampled from their natural habitats. We employed a sub-community co-culture experimental strategy to reveal both predominant and rare bacteria, which were characterized using phylogenomics an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 80 publications
(113 reference statements)
5
54
3
Order By: Relevance
“…Endophytes associated with cycad coralloid roots have been studied for more than a century mostly by methods that underestimated or did not aim to measure the non-cyanobacterial bacterial diversity present inside the root. Our study supports very early studies [4,8,9], and two more recent studies, the 16S rRNA-based Zheng et al [17] and the metagenomic-based Gutiérrez-García et al [18], that report a diverse bacterial microbiome beyond cyanobacteria.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Endophytes associated with cycad coralloid roots have been studied for more than a century mostly by methods that underestimated or did not aim to measure the non-cyanobacterial bacterial diversity present inside the root. Our study supports very early studies [4,8,9], and two more recent studies, the 16S rRNA-based Zheng et al [17] and the metagenomic-based Gutiérrez-García et al [18], that report a diverse bacterial microbiome beyond cyanobacteria.…”
Section: Discussionsupporting
confidence: 91%
“…Zheng et al [17] found significant differences in the abundance of some bacterial families compared to regular cycad roots, with a dominance of cyanobacteria in the coralloid roots [17]. Likewise, Gutiérrez-García et al [18] sampled the bacterial coralloid microbiome of Dioon edule using complete genomes and shotgun metagenomes from axenic cultures and liquid co-cultures that aim to describe the functional diversity of the endophytic microbiome [19], and also found several bacterial groups in addition to cyanobacteria endophytes. There appears to be a broad spectrum of non-cyanobacteria inside the coralloid root, which we are only beginning to explore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyanobacterial sequences from Panamanian Zamia belong to a single clade based on rb-cL-rbcX. Our study is in line with findings in the Mexican cycad genus Dioon where cyanobionts were also monophyletic using 16S rRNA (Gutiérrez-García et al, 2018;Suárez-Moo et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…To investigate microbial diversity within coralloid roots, researchers have used a broad set of techniques, including DNA restriction patterns (Lindblad, Haselkorn, Bergman, & Nierzwicki-Bauer, 1989;Lotti, Giovannetti, Margheri, Ventura, & Materassi, 1996), protein fingerprinting (Zimmerman & Rosen, 1992), PCR fingerprinting (Costa, Paulsrud, & Lindblad 1999;Costa, Romero, & Lindblad 2004;Zheng, Song, Bao, Bergman, & Rasmussen, 2002), and Sanger sequencing (Cuddy, Neilan, & Gehringer, 2012;Gehringer et al, 2010;Gutiérrez-García et al, 2018;Thajuddin et al, 2010;Yamada, Ohkubo, Miyashita, & Setoguchi, 2012). Only two studies have so far addressed the diversity of endosymbionts using metagenomic approaches (e.g., amplicon sequencing of the 16S for bacteria).…”
Section: Introductionmentioning
confidence: 99%